Rancang Bangun Sistem Penyiraman dan Perawatan Tanaman Geranium Terintegrasi Telegram - Rizki Azka Fihi Aghnia; Annisa Shafira Darmawan; Shita Fitria Nurjihan; Ardina Askum (Politeknik Negeri Jakarta, 2022)
As a tropical country, Indonesia has a rainy season where there can be mosquito breeding which is quite dangerous for humans. There are several ways to deal with it, one of which is by growing your own geranium plants at home. To make it easier to water these plants, we need a system that can do it even if the planter is not at home. Thus, a system was designed using the Internet of Things (IoT) concept, so that watering plants can be done remotely and water savings can be realized. The system consists of a NodeMCU microcontroller which is connected to the Telegram application as an interface to the user. The three sensors used as input components of the system are the DHT22 sensor to measure the ambient temperature, the soil moisture sensor to measure soil moisture, and the magnetic float sensor to measure the water supply. The output components used are water pumps and servos. The system is powered by a DC power supply with an output voltage of 12 V to power the water pump and 5 V to power the NodeMCU. The results of testing the tool show that the tool works well. The system works when the humidity level is below 80% will automatically carry out the watering process, at temperatures above 32oC the paranet can be lowered, and when the water is full or empty, the water supply can be detected accurately. NodeMCU can connect to the Telegram application with the help of a Telegram Bot library called CTBot that allows users to receive information and give orders. Keywords : soil moisture, plant watering, paranet, temperature